Employees performance and motivation: a case of manufacturing organization of Tikapur Municipality (Journal of Tikapur Multiple Campus, 2018)
This study is designed to explore the employee’s performance on the basis of motivation. Questionnaires were distributed to 100 employees from 20 manufacturing organization located in Tikapur Municipality. Descriptive statistics and correlation were used to analysis the data. Using correlation and regression equation, best employee’s performance depends salary, training, working condition and other facilities. The result showed that factor of motivation made positive effects on employee’s performance.